2022
DOI: 10.1002/ehf2.13850
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in heart failure patients: the French CARENFER prospective study

Abstract: Aims Iron deficiency (ID) is reported as one of the main co-morbidities in patients with chronic heart failure (CHF), which then influences quality of life and prognosis. The CARENFER study aimed to assess the prevalence of ID in a large panel of heart failure (HF) patients at different stages of the disease. Methods and resultsThis prospective cross-sectional nationwide study was conducted in 48 medical units in France in 2019. Serum ferritin concentration and transferrin saturation (TSAT) index were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…The CARENFER studies were conducted in France between May 2019 and June 2021. The four of them consisted of a cross-sectional, multicenter, and nationwide study carried out to determine the prevalence of ID in patients with cancer [ 17 ], HF [ 18 ], CKD [ 19 ], and IBD [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CARENFER studies were conducted in France between May 2019 and June 2021. The four of them consisted of a cross-sectional, multicenter, and nationwide study carried out to determine the prevalence of ID in patients with cancer [ 17 ], HF [ 18 ], CKD [ 19 ], and IBD [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Even if anemia is often the final consequence of ID [ 5 ], several studies showed that independently of the presence of anemia, ID appeared as a risk factor of mortality in patients with chronic HF (CHF) [ 11 , 16 ] and CKD [ 12 , 13 ]. Recently, we showed that the prevalence of ID is high in all patients with chronic inflammatory disease, independently of the presence of factors known to influence the occurrence of ID [ 17 , 18 , 19 , 20 ]. Therefore, ID should be considered an independent therapeutic objective in patients with chronic inflammatory conditions, that is, a comorbidity that should be systematically detected and treated if identified [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The French nationwide prospective CARENFER survey performed during 2019-2020 in hospitalized patients reported comparable high prevalence rates-57.9% (n = 1221) in patients with solid tumors, 49.6% (n = 1661) in CHF, 47.1% (n = 1211) in nondialyzed CKD, and 23.7% (n = 1090) in IBD [10][11][12][13].…”
Section: Iron Deficiency Is Frequent In Chronic Conditionsmentioning
confidence: 99%
“…Iron deficiency is one of the most commonly seen comorbid conditions in patients who have HF, with studies reporting that approximately 40−70% of patients with CHF have iron deficiency [ 5 , 7 , 32 , 33 , 34 , 35 , 36 ], regardless of their ejection fraction [ 9 ]. Iron deficiency also has a prevalence of up to 80% in patients with acute HF (AHF) [ 10 , 37 ].…”
Section: Why Is Diagnosing and Treating Iron Deficiency In Patients W...mentioning
confidence: 99%